WHY DO MUZAKI PAY ZAKAT THROUGH INSTITUTIONS? THE THEORY OF PLANNED BEHAVIOUR APPLICATION - Muhammad Akbar Fadzkurrahman Annahl; Ali Chamani Al Anshory; Mahdiah Aulia (Bank Indonesia, 2021)
This research investigates the factors that influence the intention of paying zakat maal through zakat institutions. By paying zakat in such a way, muzaki can support zakat institutions in eradicating poverty through a broader and deeper distribution of zakat funds. However, the realisation of zakat collection remains low compared to its potential, which means that the number of muzaki who pay zakat through institutions also remains limited. The research applied the extended theory of planned behavior (TPB) framework with knowledge, trust, and perceived ease of use as additional variables to address the issue in question. Subsequently, an online questionnaire was conducted using the purposive sampling method, which generated 383 respondents. The primary data were examined using the PLS-SEM method. Based on the results, all the proposed hypotheses were accepted. Considering that paying zakat via institutions provides a better way to assist rightful recipients, various suggestions are made to zakat managers, policymakers, and muzaki. The research highlights a new perspective by examining the intention of paying zakat maal through institutions with the additional variables of knowledge, trust, and perceived ease of use.